Implementation of Risk Management in Murabahah Financing At Bmt UGT Nusantara Nusantara Pasuruan - Eka Melinda; Segaf Segaf (Enrichment : Journal of Management, 2023)
Abstract Islamic finance is one sector that is experiencing rapid growth in the global financial industry. In its business activities, Islamic finance will certainly be faced with risks related to its function as an intermediary institution. Risk management is needed to handle, identify and manage risks that may occur. Risk management implemented at BMT UGT Nusantara Pasuruan, including risk in Murabahah financing at BMT UGT Nusantara Pasuruan. With a qualitative descriptive research model with a real phenomenon approach in the field, namely at BMT UGT Nusantara Pasuruan. The results of the research discussing the application of risk management at BMT UGT Nusantara Pasuruan include the risk management process for murabaha financing at BMT UGT Nusantara Pasuruan previously with the assistance process, namely by identifying the ability of members to return the financing. Then a risk measurement is carried out by identifying the form and value of the collateral submitted. Then handling risks, which is carried out by BMT UGT Nusantara Pasuruan, namely by rescheduling members who can still be fostered, and finally, by applying the principles of 5C analysis or (character, capacity, capital, collateral, economic condition).